Combined superoxide dismutase mimetic and peroxynitrite scavenger protects against neointima formation after endarterectomy in association with decreased proliferation and nitro-oxidative stress - Hirschberg, Kristóf; Radovits, Tamás; Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Zöllner, Stefan; Seidel, Beatrice; Páli, Szabolcs; Barnucz, Enikő; Merkely, B.; Karck, Matthias; Szabó, Gábor (European journal of vascular and endovascular surgery, 2010)
Objective - Reactive oxygen and nitrogen species (e.g., peroxynitrite) may trigger neointima formation leading to restenosis. In a rat carotid endarterectomy (CEA) model, we investigated the effects of the manganese(III)tetrakis(4-benzoic acid)porphyrin (MnTBAP), a superoxide dismutase (SOD) mimetic and peroxynitrite scavenger on neointima formation. - Methods - CEA was performed in male Sprague-Dawley rats. Animals received either vehicle (control group; n=15) or 15mg kg−1 day−1 MnTBAP intraperitoneally for 3 weeks (treatment group; n=13). Four groups of carotids were analysed: the left, uninjured carotids (sham) and the right, injured carotids (control CEA) from the control group, the right, injured carotids from the treatment group (CEA+MnTBAP) and an additional group of carotids that were harvested 1h following endarterectomy. The analysis of carotid arteries was performed by histology, immunohistochemistry and real-time polymerase chain reaction (PCR). Plasma malondialdehyde (MDA) levels were measured by lipid hydroperoxidase assay. - Results - Stenosis rate (10.5±8.1% vs. 45.4±28.3%), the percentage of proliferating cell nuclear antigen-positive cells (13.4±7.1% vs. 23.3±11.0%) and nitrotyrosine immunoreactivity (5.8±1.9 vs. 8.0±2.0) were significantly reduced in the vascular wall of the CEA+MnTBAP group compared with control CEA group. Ratio of Terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labelling (TUNEL)-positive nuclei was significantly lower after antioxidant therapy (41.7±26.7% vs. 64.9±18.5%). Plasma MDA levels increased after endarterectomy (11.7±4.8 vs. 4.1±2.0μmol l−1) and reduced in the treatment group (3.2±2.1μmol l−1). No significant gene regulation after MnTBAP treatment could be noted. - Conclusions - MnTBAP decreased neointima formation, which was associated with reduced vascular smooth muscle cell proliferation and attenuated local and systemic nitro-oxidative stress.